Board Characteristics and Intellectual Capital in Islamic Banks: Evidence from Indonesia, Malaysia and Bangladesh - Ayunda Rizqi Oktaviana; Doddy Setiawan (Falah: Jurnal Ekonomi Syariah, 2022)
This study aims to determine the effect of intellectual capital and board characteristics on Islamic banks in Indonesia, Malaysia, and Bangladesh. This study was quantitative  were data collected from the annual report of Islamic banks in 2014 to 2019 in Indonesia, Malaysia, and Bangladesh. The data were analyzed using multiple linear regression. The result found that educational diversity and gender diversity have a significant effect on intellectual capital at Islamic banks in Indonesia, Malaysia, and Bangladesh, while the board size and the board meeting does not affect. The result may have a new perspective on the relationship between the characteristics of directors and intellectual capital in Asia, especially Indonesia, Malaysia, and Bangladesh. The application of intellectual capital can increase decision-making accuracy and problem-solving so that managerial functions can improve company performance by increasing the number of directors and gender diversity.